KOMPOSIT FIBER REINFORCED PLASTIC SEBAGAI MATERIAL BODI KAPAL BERBASIS FIBERGLASS TAHAN API - Siregar, Adella Hotnyda; Setyawan, Budiman Adi; Marasabessy, Amir (Bina Teknika, 2016)
The aim of the research is to analyze resin in boat body base on composite fiber reinforced plastic with fire resistant/flame retardant. The resin used polyester resin Yucalac 157 BQTN-EX and Yucalac BQTN-FR. Experimental method is used in this research and speciment composite made with hand lay up method and then observed with flammability test UL 94 standard. The result show that composite with Yucalac 157 BQTN- FR resin higher flammability and linier burning rate less than Yucalac 157 BQTN–EX resin.